2005
DOI: 10.1016/j.ejpain.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine in painful diabetic neuropathy: a randomized, placebo‐controlled study

Abstract: In this multicentre, placebo-controlled, 16-week trial, the efficacy and safety of oxcarbazepine monotherapy in patients with neuropathic pain of diabetic origin was evaluated. Eligible patients had a 6-month to 5-year history of neuropathic pain symptoms of diabetic origin and a pain rating of > or =50 units on the visual analogue scale (VAS). Oxcarbazepine was initiated at a dose of 300 mg/day and titrated to a maximum dose of 1800 mg/day. In total, 146 patients (oxcarbazepine, n=69; placebo, n=77) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(82 citation statements)
references
References 39 publications
0
75
0
7
Order By: Relevance
“…18 -20 Two studies showed no benefit, 18,20 but a third showed a moderate benefit-17% more patients on oxcarbazepine had a Ͼ50% pain reduction compared to placebo, with an NNT of 6.023. 19 The study showing a positive response had a slightly higher completion rate (73% 19 compared to 67%). 20 Short Form-Quality of Life (SF-QOL) scores were not improved.…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…18 -20 Two studies showed no benefit, 18,20 but a third showed a moderate benefit-17% more patients on oxcarbazepine had a Ͼ50% pain reduction compared to placebo, with an NNT of 6.023. 19 The study showing a positive response had a slightly higher completion rate (73% 19 compared to 67%). 20 Short Form-Quality of Life (SF-QOL) scores were not improved.…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…121,122 Zonisamide, levetiracetam, and tiagabine At this time, no significant studies have been published reporting the benefit of these agents for chronic painful conditions.…”
Section: Oxcarbazepinementioning
confidence: 99%
“…61 Oxcarbazepine, a newer anticonvulsant structurally related to carbamazepine, may also be useful; however, only one RCT (in diabetic peripheral neuropathy) has been published. 85 Gabapentin, an α-2-delta subunit voltage-gated calciumchannel antagonist, 86 has repeatedly demonstrated analgesic Pregabalin is a gabapentin analogue with a similar mechanism, higher calcium-channel affinity and better bioavailability. 60,87 Pregabalin was superior to placebo in several RCTs in diabetic peripheral neuropathy and postherpetic neuralgia (NNT = 4.2).…”
Section: Anticonvulsantsmentioning
confidence: 99%